Die implikasies van stellings as kategorie van nie-egte vrae in Romeine - P. Verster (Acta Theologica)
This article argues that non-authentic questions have certain clear implications when used as rhetorical instruments in Paul’s Letter to the Romans. These questions are abstracted as a category in accordance with Verster (1999). In the light of Grice’s co-operative principle, the non-authentic questions which are statements, are distilled from the text and analysed. They are also subdivided into question-statements, rhetorical questions and meta-communicative rhetorical interrogatives. The implications for the author’s message are then discussed against the background of the insights derived from commentaries on Romans.